Nonlinear dynamic analysis of a four-bar mechanism having revolute joint with clearance - Sajjad Boorghan Farahan; Mohammad Reza Ghazavi; Sasan Rahmanian (Journal of Theoretical and Applied Vibration and Acoustics, 2016)
In general, joints are assumed without clearance in the dynamic analysis of multi-body echanical systems. When joint clearance is considered, the mechanism obtains two uncontrollable degrees of freedom and hence the dynamic response considerably changes. The joints’ clearances are the main sources of vibrations and noise due to the impact of the coupling parts in the joints. Therefore, the system responses lead to chaotic and unpredictable behaviors instead of being periodic and regular. In this paper, nonlinear dynamic behavior of a four-bar linkage with clearance at the joint between the coupler and the rocker is studied. The system response is performed by using a nonlinear continuous contact force model proposed by Lankarani and Nikravesh [1] and the friction effect is considered by a modified Coulomb friction law [2]. By using the Poincaré portrait, it is proven that either strange attractors or chaos exist in the system response. Numerical simulations display both periodic and chaotic motions in the system behavior. Therefore, bifurcation analysis is carried out with a change in the size of the clearance corresponding to different values of crank rotational velocities. Fast Fourier Transformation is applied to analyze the frequency spectrum of the system response.